Glymphatic dysfunction in amyotrophic lateral sclerosis: a multimodal MRI investigation of brain-CSF functional and structural dynamics - Liu, Zelin; Dong, Hui; Yang, Haiqing; Zhou, Lixia; Li, Min; Zhang, Xinyi; Zhao, Yuanhui; Han, Meiqi; Liu, Yaling; Geng, Zuojun (Frontiers in Neuroscience, 2025)
BackgroundAmyotrophic lateral sclerosis (ALS) is characterized by progressive motor neuron degeneration and glial activation. The coupling of global blood oxygen level-dependent (gBOLD) signals with cerebrospinal fluid (CSF) inflow dynamics is a novel non-invasive biomarker, which is applied to assess the relationship between lymphatic function and ALS.ObjectiveThe gBOLD-CSF coupling was used to assess the glymphatic system dysfunction related to ALS, and the relationship between this disease and the glymphatic system was further explored by combining the diffusion tensor imaging index of the perivascular space (DTI-ALPS) and the volume fraction of the choroid plexus (choroid plexus volume [CPV]/intracranial total volume [TIV]).MethodsWe conducted a systematic analysis and comparative study of the imaging indicators and clinical data of 41 patients with ALS and 43 healthy controls (HC).ResultsALS patients showed significantly reduced gBOLD-CSF coupling (p < 0.001), reduced ALPS index (p < 0.001), and increased CPV fraction (p < 0.001). The area under the ROC curve (AUC) were 0.790 (gBOLD-CSF), 0.760 (ALPS index), and 0.748 (CPV fraction). A diagnostic model for ALS was developed based on gBOLD-CSF coupling, ALPS index, and CPV fraction with an AUC of 0.897 (0.830–0.964). The calibration curve demonstrates that the model exhibits strong consistency. The results of the Decision Curve Analysis (DCA) further indicate that the nomogram possesses substantial clinical utility.ConclusionThis study identified that gBOLD-CSF coupling has diagnostic value for ALS and developed a diagnostic model by combining the ALPS index and CPV fraction, which has good diagnostic efficacy and clinical application value.